Etika Komunikasi Pejabat Publik dalam Penanganan Pandemi Covid-19 - Ahmad Fahruddin (El Madani : Jurnal Dakwah dan Komunikasi Islam, 2021)
Communication of public officials greatly influences the public to comply with the corona virus disease (Covid-19) health protocol and is positively correlated with the effectiveness of handling Covid-19. Unfortunately, as this study found using descriptive qualitative methods and data collection techniques from credible online media, there are a number of public officials who often make controversial statements about Covid-19 that are not fully based on scientific, accurate data, and empirical facts. In addition to causing ethical communication problems, this has led to pro and contra responses, noise, confusion and disrupts and hinders acceleration in handling the Covid-19 pandemic. Therefore, this study recommends that public officials pay attention to and prioritize communication ethics in handling the Covid-19 pandemic so that the Covid-19 pandemic can be controlled, and quickly removed from Indonesian soil.